DEVELOPMENT AND CHALLENGES ON CONSERVATION POLICY AND LAWMAKING IN THE CORAL TRIANGLE REGION - M. Safnan Mardhatillah; Nellyana Roesa (Fakultas Hukum Universitas Syiah Kuala, 2018)
The research aims to determine the current environmental policy used in the Coral Triangle to mitigate the combined and immediate threats from destructive fishing, bycatch, and climate change, as well as examining the challenges in protecting coral reefs and activities in the Coral Triangle. The method used in the research is Normative Research Method. The thesis found that the six countries in the Coral Triangle has established a joint initiative named Coral Triangle Initiative Declaration on Coral Reefs, Fisheries, and Food Security (CTI-CFF) to help solving the problem. The initiative has been involved in the creation of MPA networks, capacity building, and fisheries management. However, there are multiple issues in the conservation programs, which includes differences in economic power and customs, weak governance, and poor enforcements. The six countries need to establish programs which will work across the region, not just at national level. They also have to raise the commitment to enforcement along the region, and connect programs from local to national level.